Circadian Variation of Migraine Attack Onset Affects fMRI Brain Response to Fearful Faces - Baksa, Daniel; Szabo, Edina; Kocsel, Natalia; Galambos, Attila; Edes, Andrea Edit; Pap, Dorottya; Zsombok, Terezia; Magyar, Mate; Gecse, Kinga; Dobos, Dora; Kozak, Lajos Rudolf; Bagdy, Gyorgy; et al. (Frontiers in Human Neuroscience, 2022)
Background: Previous studies suggested a circadian variation of migraine attack onset, although, with contradictory results – possibly because of the existence of migraine subgroups with different circadian attack onset peaks. Migraine is primarily a brain disorder, and if the diversity in daily distribution of migraine attack onset reflects an important aspect of migraine, it may also associate with interictal brain activity. Our goal was to assess brain activity differences in episodic migraine subgroups who were classified according to their typical circadian peak of attack onset. Methods: Two fMRI studies were conducted with migraine without aura patients (n=31 in Study 1, n=48 in Study 2). Among them, three subgroups emerged with typical Morning, Evening, and Varying start of attack onset. Whole brain activity was compared between the groups in an implicit emotional processing fMRI task, comparing fearful, sad and happy facial stimuli to neutral ones. Results: In both studies, significantly increased neural activation was detected to fearful (but not sad or happy) faces. In Study 1, the Evening start group showed increased activation compared to the Morning start group in regions involved in emotional, self-referential (left posterior cingulate gyrus, right precuneus), pain (including left middle cingulate, left postcentral, left supramarginal gyri, right Rolandic operculum) and sensory (including bilateral superior temporal gyrus, right Heschl’s gyrus) processing. While in Study 2, the Morning start group showed increased activation compared to the Varying start group at a nominally significant level in regions with pain (right precentral gyrus, right supplementary motor area) and sensory processing (bilateral paracentral lobule) functions. Conclusion: Our fMRI studies suggest that different circadian attack onset peaks are associated with interictal brain activity differences indicating heterogeneity within migraine patients and alterations in sensitivity to threatening fearful stimuli. Circadian variation of migraine attack onset may be an important characteristic to address in future studies and migraine prophylaxis.